Sujeito, natureza e sociedade: uma análise pitagórica e transdisciplinar da educação - Schmidt Neto, Álvaro A. (2009)
This research intends to link the Pythagorean cosmogony of the tetraktys with the transdisciplinar education conception. Getting from the analysis of the symbolism of Pythagorean tetraktys s numbers and from the complex thought, the research investigates the possibility of a greater integration and strengthening of the existing relationships between the subject, the nature and the other (society). These relationships and interdependences between the subject, the nature and the other (society), also known as life triangle, are related with the Pythagorean cosmology, which set out the development of the beings in a cyclical and recursive process. This movement involves the identity of the subject, the environment and the relationships the subject establishes with this environment in search of his integration and his development. The research also presents the possibility of application of this theoretical construction in the educational field, offering didactic suggestions for a learning process connected with the idea of the creation itself and the development of the beings